Effects of surfactant on geotechnical characteristics of silty soil - Rahman, Z.A.; Sahibin, A.R.; Lihan, T.; Idris, W.M.R.; Sakina, M. (Universiti Kebangsaan Malaysia, 2013)
Surfactants are often used as a cleaning agent for restoration of oil-contaminated soil. However the effect of surfactant on the geotechnical properties of soil is not clearly understood. In this study, the effects of surfactant on silty soil were investigated for consistency index, compaction, permeability and shear strength. Sodium dodecyl sulfate (SDS) was used in this study to prepare the surfactant-treated soil. Our results showed that the soil with added surfactant exhibited a decrease in liquid and plastic limit values. Maximum dry densities increased and optimum moisture contents decreased as contents of added surfactant were increased. The presence of surfactant assists the soil to achieve maximum density at lower water content. The addition of surfactant decreased the permeability of soil from 6.29×10-4 to 1.15×10-4 ms-1. The shear strength of soil with added surfactant was examined using the undrained unconsolidated triaxial tests. The results showed that the undrained shear strength, Cu was significantly affected, decreased from 319 kPa to 50 kPa for soil with 20% of added surfactant. The results of this study showed that the presence of surfactant in soil can modify the mechanical behaviour of the soil.